The Effect of Profitability on Debt Policy with Dividend Policy as a Moderating Variable - Ni Kadek Sintya Pratiwi; Dewa Gede Wirama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Profitability is one of the key indicators in assessing a company's ability to generate profits and plays a crucial role in financial decision-making. According to the pecking order theory, companies with high profitability tend to prefer using internal funds and reduce reliance on debt. This study aims to analyze the effect of profitability on debt policy, as well as to examine the role of dividend policy as a moderating variable in this relationship. The study employed Slovin’s formula for sample selection and analyzed 263 non-financial publicly listed companies on the Indonesia Stock Exchange (IDX) in 2023. The data used in this research were secondary data obtained from annual financial reports published on the official website of the IDX or the respective company websites. Profitability was measured using return on assets (ROA), debt policy was measured by the debt-to-equity ratio (DER), and dividend policy was measured by the dividend payout ratio (DPR). The analytical method used in this study was multiple linear regression analysis with the help of the SPSS software. The results indicate that profitability has a negative effect on debt policy, meaning that the more profitable a company is, the less likely it is to depend on debt financing. Additionally, the findings suggest that dividend policy does not significantly moderate the relationship between profitability and debt policy. This implies that whether a company distributes dividends or not does not meaningfully influence how profitability affects its debt decisions. These results are in line with the pecking order theory and provide insight for corporate financial managers in planning funding structures. It also emphasizes the importance of internally generated funds for companies with strong earnings performance.